The regime of Demetrius of Phalerum in Athens, 317-307 BCE : a philosopher in politics - O'Sullivan, Lara (Brill, 2009)
This work draws upon a close re-examination of the literary and epigraphic evidence to offer new understandings of Athenian history during the decade-long rule (317-307 BCE) of the accomplished Peripatetic scholar and renowned legislator, Demetrius of Phalerum.
Keywords: Demetrius, -- of Phaleron, -- approximately 350 B.C.-; Demetrius, -- of Phaleron, -- approximately 350 B.C.- -- Political and social views.; Demetrius -- Phalereus.; Governors -- Greece -- Athens -- Biography.; Statesmen -- Greece -- Athens -- Biography.; Orators -- Greece -- Athens -- Biography.; Philosophers, Ancient -- Biography.; Athens (Greece) -- Politics and government.; Philosophy, Ancient.; Athens (Greece) -- Relations -- Macedonia.; Macedonia -- Relations -- Greece -- Athens.; Gouverneurs -- Grèce -- Athènes -- Biographies.; Hommes d'État -- Grèce -- Athènes -- Biographies.; Orateurs -- Grèce -- Athènes -- Biographies.; Philosophes anciens -- Biographies.; Philosophie ancienne.; Macédoine -- Relations -- Grèce -- Athènes.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY -- Ancient.; Governors; International relations; Orators; Philosophers, Ancient; Philosophy, Ancient; Political and social views; Politics and government; Statesmen; Europe -- Macedonia; Greece -- Athens; Athen; Biography; Biographies; Biographies.